A prospective, cross-over randomized controlled trial to determine whether end stage renal disease patients receiving chronic renal replacement therapy at Charlotte Maxeke Johannesburg Academic Hospital are more likely to have an improved lipid profile after including plant sterols as part of their dietary intake for eight weeks - Ribeiro, Nicole Pereira (Stellenbosch : Stellenbosch University, 2016)
Thesis (MNutr)--Stellenbosch University, 2016.